Pengaruh Religiusitas Terhadap Penggunaan Gawai yang Bermasalah: Peran Kontrol Diri dan Stres Pada Mahasiswa - Hariz Enggar Wijaya; Syafira Anantasya Agsanda Putri; Zulfa Firdausi; Nida Nur Nabila (Psychosophia: Journal of Psychology, Religion, and Humanity, 2021)
Smartphone use is increasing worldwide. Despite the benefit of using a smartphone, a growing body of research has reported smartphone use's negative effect. Lack of self-control has been associated with problematic use of smartphones as well as stress. However, there is still little evidence of how religiosity could have an impact on problematic smartphone use. This study aimed to examine the indirect effect of religiosity on problematic smartphone use via self-control and stress. A few 146 undergraduate students enrolled in this study. They completed an online survey comprising problematic smartphone use, religiosity, self-control, and stress. Our findings showed a negative association between religiosity or self-control with problematic smartphone use. Stress also correlated positively with problematic smartphone use. Path analysis demonstrated the mediation effect of self-control on religiosity and problematic smartphone use, but not the stress. These results underlined the psychological mechanism underlying smartphone use of students. Moreover, religiosity could be considered to prevent the detrimental effect of problematic smartphone use.